Consumer Protection Related To The Increasing Prevalence Of E-Cigarettes In Makassar City, Legal Perspectives And Awareness User - Munawar; Sodikin (PT. Anagata Sembagi Education, 2024)
E-cigarettes have become a growing global phenomenon, including in Indonesia. Makassar is one of the cities with the highest number of e-cigarette outlets, reaching more than 150, according to data from the Indonesian Youth Council for Tobacco Control (IYCTC). However, the increasing prevalence of e-cigarettes poses new challenges related to consumer protection, especially in terms of product information and its safety. This research aims to analyze consumer rights violations, evaluate the level of public knowledge, and recommend consumer protection strategies. Using a qualitative descriptive approach, data is collected through interviews, surveys, and document analysis. The results of the study show that there are violations of consumer rights in the form of misleading product information, low public awareness about health risks, and lack of adequate regulations. Recommendations include strengthening regulations, public education, and stricter supervision of product promotion and distribution